Extracellular vesicles: A potential future strategy for dental and maxillofacial tissue repair and regeneration - Liu, Ziwei; Wang, Situo; Huo, Na; Yang, Shuo; Shi, Quan; Xu, Juan (Frontiers in Physiology, 2022)
Extracellular vesicles (EVs), nano-sized bilayer membrane structures containing lipids, proteins and nucleic acids, play key roles in intercellular communication. Compared to stem cells, EVs have lower tumorigenicity and immunogenicity, are easier to manage and cause fewer ethic problems. In recent years, EVs have emerged as a potential solution for tissue regeneration in stomatology through cell-free therapies. The present review focuses on the role of EVs in dental and maxillofacial tissue repair and regeneration, including in dental and periodontal tissue, maxilla and mandible bone, temporomandibular joint cartilage, peripheral nerve and soft tissue. We also make a brief overview on the mechanism of EVs performing functions. However, limitations and challenges in clinical application of EVs still exist and should be addressed in future researches.